Hydrophilic surface molecularly imprinted naringin prepared via reverse atom transfer radical polymerization with excellent recognition ability in a pure aqueous phase. Issue 45 (26th May 2017) - Feng, Xuexue; Wu, Tielei; Yu, Bingqing; Wang, Yan; Zhong, Shian
Abstract : An easy and highly efficient method using hydrophilic surface molecularly imprinted polymers (SMIPs) for the selective recognition of naringin from pure aqueous solution was developed. Abstract : An easy and highly efficient method using hydrophilic surface molecularly imprinted polymers (SMIPs) for the selective recognition of naringin from pure aqueous solution was developed. A macroporous support using metal organic gels (MOGs) as the porogen was initially synthesized. Then, surface-initiated reverse atom-transfer radical polymerization (R-ATRP) was performed on the support surface. Finally, hydrophilic SMIPs with abundant molecular imprinting recognition sites were obtained. The SMIPs were characterized by infrared spectroscopy, high performance liquid chromatography, thermogravimetry, scanning electronic microscopy, static contact angle analysis, and nitrogen adsorption–desorption measurements. The aqueous extraction solution can be directly absorbed by SMIPs without adjusting pH and adsorption can occur under neutral conditions. Equilibrium adsorption was reached rapidly within 3 min, and the maximum equilibrium binding capacities of SMIPs were found to be 63.54 μmol g −1 for naringin. Selective analysis indicated a high selectivity of SMIPs towards template naringin over hesperidin and rutin. Extraction experiments suggested excellent separation and purification of naringin in an aqueous grapefruit extract, with a recovery rate of 93% and at least thrice usage of SMIPs.